Role of Arachidonic Acid and Its Metabolites in the Priming of NADPH Oxidase in Human Polymorphonuclear Leukocytes by Peritoneal Dialysis Effluent - Daniels, I. (American Society for Microbiology, 1998)
Peritoneal dialysis effluent (PDE) contains a low-molecular-weight solute that will activate and prime the NADPH oxidase of human neutrophils via a phospholipase A(2) (PLA(2))-dependent mechanism. Since the products of PLA(2) are known to activate and prime the oxidase we have investigated their role in the dialysis effluent-mediated activation and priming of human neutrophils. NADPH oxidase activity of PDE-primed and -unprimed neutrophils was measured by lucigenin-enhanced chemiluminescence in the presence of known inhibitors of the arachidonic acid cascade. Incubation of neutrophils with the nonselective PLA(2) inhibitor quinacrine (0 to 100 μM) reduced oxidase activity in both primed and unprimed cells. Furthermore, primed cells were more sensitive to the action of quinacrine than were unprimed cells. We were unable to determine the relative roles of secretory PLA(2) (sPLA(2)) and cytosolic PLA(2) (cPLA(2)) since the selective sPLA(2) inhibitor scalaradial (0 to 100 μM) inhibited oxidase activity in both groups of cells by similar degrees, while the specific cPLA(2) inhibitor AACO-CF(3) (0 to 50 μM) failed to affect activity in either group. Inhibition of platelet-activating factor (PAF), cycloxygenase, and 5-lipoxygenase-activating protein by hexanolamino-PAF (0 to 25 μM), flurbiprofen (0 to 25 μM), and MK886 (0 to 5 μM), respectively, had no effect upon oxidase activity. However, the direct inhibition of 5-lipoxygenase by caffeic acid or lipoxin A(4) resulted in a similar concentration-dependent attenuation of oxidase activity in both primed and unprimed cells. Leukotriene B(4) (LTB(4)) release from primed neutrophils was comparable to that from unprimed cells with the exception of phorbol myristate acetate-stimulated cells, which released fivefold more LTB(4) than control. Taken together, these results suggest that it is arachidonic acid per se, and not its metabolites, that is important in priming of the neutrophil NADPH oxidase by dialysis effluent.